Effect of Variation of Johnson-Cook Parameters on Kinetic Energy and Simulation of 4340 Steel Projectile. (2018) - Thakur, Nitin; Kumar, Pramod; Singh Bharj, Rabinder
Abstract: Computer simulations have been used for decades in the modelling of high velocity impact and general large deformation problems. Several computer codes have been developed to simulate these types of problems under a variety of geometric conditions and for any variety of materials. The Johnson-Cook material model is widely used in the simulation of high velocity impacts and even penetration of target structures. This research work represents the study of effects of variation of Johnson-Cook material constants on ballistic impact and its effect on residual kinetic energy of projectile. In the Johnson-Cook damage model, there are five material constants viz. D1, D2, D3, D4 and D5, and it is very difficult to find out all of these material constants by experiments. The main objective of the present research is to determine the most sensitive parameter out of these constants. To accomplish this target, experimental testing was done and additionally the impact physics was likewise recreated numerically utilizing ABAQUS. For the impact phenomenon 4340 steel, 10 mm diameter projectile and a 1006 steel target plate were chosen. From this study, it is concluded that the most sensitive Johnson-Cook damage model constant is 'D3'